Temperature Dependence of the Zero-Field In-Plane Critical Current Density of YBa2Cu3O7-d High-Tc Superconductors - Sarkar, M. R. H.; Naqib, S. H. (Journal of Scientific Research, 2012)
The nature of the temperature dependence of the zero-field critical current density, Jc0(T), in the CuO2 planes has been investigated for c-axis oriented YBa2Cu3O7-d (Y123) thin films over a range of hole content, p. The hole concentration was varied by changing the oxygen deficiency, d, in the CuO1-d chains by annealing the films under different oxygen partial pressures and temperatures. The Jc0(T) values were extracted from the magnetic hysteresis (M-H) loops obtained at different temperatures. From the analysis of the Jc0(T) data for different sample compositions, we have extracted valuable information regarding the nature of the underlying magnetic flux pinning mechanisms in Y123 superconductors. We have found that the oxygen defects play only a secondary role in pinning of the vortices, the superfluid density, on the other hand plays a significant role. The exponent, n, governing the Jc0(T) behavior for a given sample composition showed a systematic behavior as hole contents are changed. Keywords: Y123 superconductors; Critical current density; Flux pinning. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.9653 J. Sci. Res. 4 (2), 287-296 (2012)